(untitled) (Al-Qamar, 2021)
Fruits are the great gift of nature and the greatest of the blessings that the Creator of the Earth and Heavens has created for His servants, which have been used since human creation, which are still an important part of human diet. Some of them are heavenly fruits. They are mentioned in the Holy Qur’an, due to which they have a distinct advantage over other earthly fruits, but at the same time, due to their mention in the hadith, their superiority has increased. And the Holy Prophet (peace and blessings of Allah be upon him) has explained his economic, social, nutritional, medical and religious interpretations through his words, actions and speech due to the fact that all fruits are different from each other in terms of their importance and usefulness, color, fragrance and taste. Innumerable features and benefits are hidden in it. In view of this importance, the prophetic interpretations of these fruits cannot be ignored.